1997
DOI: 10.1128/jb.179.5.1684-1689.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the haemocin immunity gene of Haemophilus influenzae

Abstract: The bacteriocin haemocin is produced by most type b strains of Haemophilus influenzae, including strains of diverse genetic lineage, and is toxic to virtually all nontypeable H. influenzae strains. An H. influenzae transformant bearing a plasmid with a 1.5-kbp chromosomal fragment capable of conferring haemocin immunity on a haemocin-susceptible H. influenzae mutant was selected by using partially purified haemocin. Deletional and site-directed mutagenesis localized the haemocin immunity gene to the 3 open rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…However, when the H. paragallinarum hmcI gene was cloned into the same vector (pGEM-T Easy, Promega) the resulting plasmid was unable to protect against haemocinmediated killing (data not shown), suggesting that the H. paragallinarum hmcI gene does not have a promoter immediately upstream. Differences in the s 70 210 region identified by Murley et al (1997) (TAAAAAT) and the same region of the H. paragallinarum sequence (TAAATTT) or the as-yet-unidentified 235 region of the gene may account for the lack of expression from the H. paragallinarum construct in E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, when the H. paragallinarum hmcI gene was cloned into the same vector (pGEM-T Easy, Promega) the resulting plasmid was unable to protect against haemocinmediated killing (data not shown), suggesting that the H. paragallinarum hmcI gene does not have a promoter immediately upstream. Differences in the s 70 210 region identified by Murley et al (1997) (TAAAAAT) and the same region of the H. paragallinarum sequence (TAAATTT) or the as-yet-unidentified 235 region of the gene may account for the lack of expression from the H. paragallinarum construct in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…The HmcI proteins also share homology with an uncharacterized protein from Mesorhizobium loti (31 % identity, 53 % similarity, NP 108470). Murley et al (1997) identified a s 70 210 region but could not identify a 235 region upstream of the H. influenzae hmcI transcription start site and showed that the HmcI protein could be expressed from this promoter in E. coli and provide protection from haemocin-mediated killing. However, when the H. paragallinarum hmcI gene was cloned into the same vector (pGEM-T Easy, Promega) the resulting plasmid was unable to protect against haemocinmediated killing (data not shown), suggesting that the H. paragallinarum hmcI gene does not have a promoter immediately upstream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…previously described the cloning and characterization of hmd, the H M C immunity gene (Murley et al, 1997); however, little is known about the genes responsible for genetically diverse bymultilocus enzyme electrophoresis (Musser et al, 1986), produce the bacteriocin haemocin (HMC), which is toxic in vitro to virtually all non-type b strains of H . influenzae, both encapsulated and nonencapsulated (LiPuma et al, 1990;Venezia & Robertson, 1975;Venezia et al, 1977).…”
Section: Introductionmentioning
confidence: 99%